Emergency laparoscopic resection of spontaneous rupture of hepatocellular carcinoma: A case report - Allim Khairuddin; Guang, Hong Ong; Jun, Sam Tan; Syamim Johan; Vee, Chuan Hoe; Mohd Sharifudin Sharif; Firdaus Hayati (https://doi.org/10.1016/j.ijscr.2019.11.055, 2020)
INTRODUCTION: Laparoscopic liver resection is currently performed as a therapeutic modality in hepatocellular carcinoma (HCC). In an emergency setting such as bleeding or rupture, however it has not been well documented. PRESENTATION OF CASE: We describe a 55-year-old lady who presented to the emergency department with epigastric pain and symptoms of anemia for one day duration. She was normotensive but tachycardic. Blood investigations revealed hemoglobin level of 6.5 g/dL and serum alphafetoprotein of 3136 g/dL. Contrast enhanced computed tomography scan revealed ruptured HCC of segment 2 and 3. She underwent emergency laparoscopic resection of the ruptured HCC. The postoperative recovery was uneventful and she was discharged well on postoperative day 7. Histology confirmed a 10 cm ruptured HCC with 3 mm tumorfree resection margin. DISCUSSION: Ruptured HCC is associated with a high mortality rate of 25–75 %. Traditional treatment involves initial stabilization and hemostasis through trans arterial embolization followed by staged hepatic resection. However, laparoscopic liver resection has been shown to be superior than open surgery in terms of postoperative outcomes. CONCLUSION: Laparoscopic resection of bleeding HCC is achievable and can be considered in the treatment algorithm of selected patients.